OK, so where am I going wrong here?

Simplify:

So I converted into

=

=

=

But I'm told the answer is: or so, obviously I cannot do the conversion (why?)

So I did it without the conversion:

Simplify:

=

=

and here's where I'm lost: =

3 posts
• Page **1** of **1**

OK, so where am I going wrong here?

Simplify:

So I converted into

=

=

=

But I'm told the answer is: or so, obviously I cannot do the conversion (why?)

So I did it without the conversion:

Simplify:

=

=

and here's where I'm lost: =

Simplify:

So I converted into

=

=

=

But I'm told the answer is: or so, obviously I cannot do the conversion (why?)

So I did it without the conversion:

Simplify:

=

=

and here's where I'm lost: =

- EdSewersPark
**Posts:**22**Joined:**Mon May 23, 2011 8:30 pm

Simplify: ( 2^(1/4) + 8^!1/4))^2

(2^(1/4))^2 = 4^(1/4) = sqrt (2)

16^(1/4) = 2 (twice)

64^(1/4) =sqrt 8 = 2*sqrt (2)

the sum is: sqrt (2) + 2 + 2 + 2 * sqrt(2) = 4 + 3 * sqrt (2).

(2^(1/4))^2 = 4^(1/4) = sqrt (2)

16^(1/4) = 2 (twice)

64^(1/4) =sqrt 8 = 2*sqrt (2)

the sum is: sqrt (2) + 2 + 2 + 2 * sqrt(2) = 4 + 3 * sqrt (2).

- Luke53
**Posts:**54**Joined:**Sun Mar 13, 2011 9:46 am

Aha, these are the mistakes I make every time.

- EdSewersPark
**Posts:**22**Joined:**Mon May 23, 2011 8:30 pm

3 posts
• Page **1** of **1**